Epigenetic Alterations in Cancer: The Therapeutic Potential of Epigenetic Drugs in Cancer Therapy - Preeti Gupta (Drugs and Drug Candidates)
To date, numerous studies have emerged that indicate the possible role of epigenetic modulation in the development and progression of several diseases, including cancer. Epigenetic alterations participate in various steps of carcinogenesis. They play important regulatory roles in processes like cell division, proliferation, angiogenesis, and metastasis. Thus, epigenetic modifications such as DNA methylation, histone modifications, and non-coding RNAs serve as attractive and promising targets for cancer prevention and anti-cancer therapy. Epigenetic drugs or epi-drugs possess the ability to reverse many such epigenetic alterations and thus can help manage the clinical manifestations of cancer. Epigenetic drugs broadly target epigenetic modifications, including DNA methylation and histone post-translational modifications, to manifest their effects. Several naturally occurring as well as chemically synthesized compounds have been recognized as epigenetic drugs. Some of them are clinically approved, while many are in their preclinical and clinical trials. In this review, we aim to present a broad overview of the epigenetic modifications implicated in carcinogenesis. The review also compiles various epigenetic drugs that are approved for clinical practice, as well as those that are in the preclinical and clinical stages of investigation for anti-cancer therapy.